Proton pump inhibitors - possible side effects of long-term therapy: a review - Kowalewski, Jan; Bęben, Damian; Pyc, Grzegorz; Kowalewski , Łukasz (Quality in Sport, 2024)
Introduction and purpose: Proton pump inhibitors (PPIs), which have been on the market for more than 30 years, are widely regarded as safe and effective medications. For this reason, they are very popular with both doctors and patients. PPIs find their use in the treatment of such ailments as gastroesophageal reflux, gastric ulcer disease or as a shielding therapy when taking non-steroidal anti-inflammatory drugs. Nevertheless, their long-term use may be associated with many side effects. The purpose of our review is to summarize the knowledge in the current medical literature on the possible complications of chronic use of PPIs. The review is based on 30 articles from the most recent publications on chronic PPI treatment. Publications were searched for the words PPI chronic therapy, gastric cancer, omeprazole in PubMed databases. Articles from 2018-2024 represent 70% of all publications from the references. A brief description of the state of knowledge: Although the use of PPIs in the short term is relatively safe, the number of people taking these drugs has increased significantly in recent years. They are prescribed not always as indicated, patients often take them for too long - this in turn leads to an increasing incidence of side effects. Some of them can permanently affect health and significantly reduce the comfort of life - such as kidney diseases, cardiovascular disorders or gastric cancer. Summary: Considering the widespread availability and popularity of PPIs, it is important to adequately educate both patients and healthcare professionals of the possible side effects. It is crucial to use medications as prescribed, with an appropriate assessment of the risk-benefit ratio. It might result in reducing health care expenditures to deal with the consequences of IPP therapy.